The Role of Foreign Capital Invested in the Form of Foreign Direct Investment in the Economy of the Opolskie Voivodship in the Years 1990–2015 - Maria Bernat (Barometr Regionalny, 2016)
The article provides an assessment of the role of FDI in the regional economy based on the levels of economic efficiency: structural changes of the economy, economic stimulating activity, employment, modernization of the production apparatus and exchange with foreign countries. The following considerations seek to answer the questions to what extent has FDI become a catalyst for economic growth in the region and has it been a tool for benefiting the investors. The author drew attention to the effects generated by foreign companies in the domestic environment and their response to the global economic crisis.